2018
DOI: 10.1002/jcb.27936
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin/ChemR23 axis triggers an inflammatory response in keratinocytes through ROS‐sirt1‐NF‐κB signaling

Abstract: Psoriasis is a chronic disease which carries the emotional and social burden, promotes joint disability and raises comorbidity possibility in patients. Obesity is closely correlated with the occurrence of psoriasis and adipokines produced by adipose tissues were found to be critical culprits. Chemerin is one of them and its expression was increased in patients with psoriatic arthritis. In our hypothesis, chemerin might act on keratinocytes and promote an inflammatory response, which plays an essential role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…kidney (Kim et al, 2019). In the ischemia-reperfusion AKI model, SIRT1 targets the deoxyacetylation of p53, FoxO1, and NF-κB to regulate the stress response, inflammation, cell senescence, and apoptosis (Grabowska et al, 2017;Zhang et al, 2017;Abdolvahabi et al, 2019;Wang et al, 2019). In addition, SIRT1mediated inhibition of tubular cell apoptosis has been shown to be the primary mechanism of renal protection (Liao et al, 2019;Ryu et al, 2019;Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…kidney (Kim et al, 2019). In the ischemia-reperfusion AKI model, SIRT1 targets the deoxyacetylation of p53, FoxO1, and NF-κB to regulate the stress response, inflammation, cell senescence, and apoptosis (Grabowska et al, 2017;Zhang et al, 2017;Abdolvahabi et al, 2019;Wang et al, 2019). In addition, SIRT1mediated inhibition of tubular cell apoptosis has been shown to be the primary mechanism of renal protection (Liao et al, 2019;Ryu et al, 2019;Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is one of the most widely studied sirtuins in kidney. It inhibits cell apoptosis, inflammation, and fibrosis by targeting the deacetylation of p53, FoxO1, and NF-κB, and hence functions in protecting cells (Kim and Lee, 2015;Phillipson-Weiner et al, 2016;Wang et al, 2017Wang et al, , 2019Zhang et al, 2017;Morigi et al, 2018;Sun et al, 2018;Abdolvahabi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SIRT1 protects fibroblasts of individuals with psoriasis from oxidative stress-induced apoptosis and restores both mitochondrial function and redox balance via downregulation of MAPK signaling [12]. Additionally, Wang Y et al reported that chemerin exacerbated psoriasiform dermatitis in a mouse model and that it can induce inflammatory response and promote NF-κB activation by inhibiting the activity of ROS-induced SIRT1 [27]. Recently, a study found that the expression levels of SIRT1-5 were downregulated, while those of SIRT6 and SIRT7 were upregulated in psoriasis skin lesions [28].…”
Section: Ros Mainly Include Superoxide Anion (O 2 −mentioning
confidence: 99%
“…Furthermore, NF-κB induces the production of IL-17 and TNF-α, thereby enhancing the downstream inflammatory response [44,46]. SIRT1 has been shown to suppress NF-κB signaling through deacetylation of the p65 subunit of NF-κB and resulting in the reduction of inflammatory responses [47]; overexpression of SIRT1 reduced the expression of IL-1β, IL-8, and TNF-α [27]. It has been recognized that SIRT1 can inhibit NF-κB signaling through AMPK, PGC-1α, and PPARα; concomitantly, NF-κB also downregulated SIRT1 expression and signaling via ROS, IFN-γ, and PARP-1 under oxidative stress conditions [48].…”
Section: Sirt1/nf-κb Relationshipmentioning
confidence: 99%
“…As mentioned above, chemerin potentially has the functions within keratinocytes and adipocytes which could induce an inflammatory response in psoriatic epidermis and adipose tissue. To validate this hypothesis, Wang et al used the HaCaT cells and the primary human keratinocytes which were treated with chemerin previously and showed that chemerin could facilitate the secretion of inflammatory factors, including IL-1β, IL-8, TNF-α, and subsequently activate the NF-κB signaling pathway through the chemerin receptors [72]. Meanwhile, chemerin significantly reduced the expression level and constrained the deacetylase activity of SIRT1 through augmentation of reactive oxygen species (ROS) production.…”
Section: Adipokines Are Pathogenic Factors Which Link Psoriasis and Omentioning
confidence: 99%